PENGARUH TINGKAT PENDIDIKAN, PENGALAMAN KERJA, PELATIHAN DAN PENGGUNAAN TEKNOLOGI INFORMASI TERHADAP KUALITAS LAPORAN KEUANGAN - Deze, Beteranda Maria Yasinta; Sayang, Sabulon; Kapa, Sesilianus (Program Studi Akuntansi Universitas Flores, 2023)
The purpose of this study was to determine the effect of education level, work experience, training and use of information technology on the financial reports of BUMDes in Bajawa District, Ngada Regency. The population in this study were BUMDes administrators in Bajawa District, totaling 10 villages in one village consisting of 3 BUMDes administrators, so the total population is 30 people. The sampling technique in this study was carried out using saturated sampling technique or total sampling, which is a sampling technique where the number of samples is equal to the population. This type of research uses quantitative research. This study uses primary data, namely a questionnaire. Data were analyzed using multiple linear regression analysis which was processed using IBM SPSS Statistics ver 25. The results of this study indicate that: (1) The level of education affects the quality of financial reports. This is evidenced by the coefficient value of the education level variable of 0.248 with tcount> ttable (2.533 > 2.059) and a significant level of 0.018 <0.05. (2) Work experience affects the quality of financial reports. This is evidenced by the coefficient value of the work experience variable of 0.256 with tcount> ttable (2.425 > 2.059) and a significant level of 0.023 <0.05. (3) Training affects the quality of financial reports. This is evidenced by the coefficient value of the training variable of 0.273 with tcount > ttable (2.294 > 2.059) and a significant level of 0.030 <0.05. (4) The use of information technology affects the quality of financial reports. This is evidenced by the variable coefficient value of the use of information technology of 0.325 with tcount> ttable (2.691 > 2.059) and a significant level of 0.013 <0.05. Simultaneously each variable of education level, work experience, training, and use of information technology has an effect on financial reports, namely the use of information technology has an effect on financial reports, namely 48.8% and the remaining 51.2% is influenced by other variables not included in the study.